Effects of continuous triiodothyronine infusion on the tricarboxylic acid cycle in the normal immature swine heart under extracorporeal membrane oxygenation in vivo - Kajimoto, Masaki (American Physiological Society, 2014)
Extracorporeal membrane oxygenation (ECMO) is frequently used in infants with postoperative cardiopulmonary failure. ECMO also suppresses circulating triiodothyronine (T(3)) levels and modifies myocardial metabolism. We assessed the hypothesis that T(3) supplementation reverses ECMO-induced metabolic abnormalities in the immature heart. Twenty-two male Yorkshire pigs (age: 25–38 days) with ECMO received [2-(13)C]lactate, [2,4,6,8-(13)C(4)]octanoate (medium-chain fatty acid), and [U-(13)C]long-chain fatty acids as metabolic tracers either systemically (totally physiological intracoronary concentration) or directly into the coronary artery (high substrate concentration) for the last 60 min of each protocol. NMR analysis of left ventricular tissue determined the fractional contribution of these substrates to the tricarboxylic acid cycle. Fifty percent of the pigs in each group received intravenous T(3) supplement (bolus at 0.6 μg/kg and then continuous infusion at 0.2 μg·kg(−1)·h(−1)) during ECMO. Under both substrate loading conditions, T(3) significantly increased the fractional contribution of lactate with a marginal increase in the fractional contribution of octanoate. Both T(3) and high substrate provision increased the myocardial energy status, as indexed by phosphocreatine concentration/ATP concentration. In conclusion, T(3) supplementation promoted lactate metabolism to the tricarboxylic acid cycle during ECMO, suggesting that T(3) releases the inhibition of pyruvate dehydrogenase. Manipulation of substrate utilization by T(3) may be used therapeutically during ECMO to improve the resting energy state and facilitate weaning.